ABCs of IBM z/OS system programming. - Gilberto Biondo, Jose (IBM redbooks., 2018)
Abstract The ABCs of IBM z/OS® System Programming is a 13-volume collection that provides an introduction to the z/OS operating system and the hardware architecture. Whether you are a beginner or an experienced system programmer, the ABCs collection provides the information that you need to start your research into z/OS and related subjects. The ABCs collection serves as a powerful technical tool to help you become more familiar with z/OS in your current environment, or to help you evaluate platforms to consolidate your e-business applications. This edition is updated to z/OS Version 2 Release 3. The other volumes contain the following content: Volume 1: Introduction to z/OS and storage concepts, TSO/E, ISPF, JCL, SDSF, and z/OS delivery and installation Volume 2: z/OS implementation and daily maintenance, defining subsystems, IBM Job Entry Subsystem 2 (JES2) and JES3, link pack area (LPA), LNKLST, authorized libraries, System Modification Program Extended (SMP/E), IBM Language Environment Volume 4: Communication Server, TCP/IP, and IBM VTAM® Volume 5: Base and IBM Parallel Sysplex®, System Logger, Resource Recovery Services (RRS), global resource serialization (GRS), z/OS system operations, automatic restart manager (ARM), IBM Geographically Dispersed Parallel Sysplex™ (IBM GDPS) Volume 6: Introduction to security, IBM RACF®, Digital certificates and PKI, Kerberos, cryptography and z990 integrated cryptography, zSeries firewall technologies, LDAP, and Enterprise Identity Mapping (EIM) Volume 7: Printing in a z/OS environment, Infoprint Server, and Infoprint Central Volume 8: An introduction to z/OS problem diagnosis Volume 9: z/OS UNIX System Services Volume 10: Introduction to IBM z/Architecture®, the IBM Z platform, IBM Z connectivity, LPAR concepts, HCD, and DS Storage Solution. Volume 11: Capacity planning, performance management, WLM, IBM RMF™, and SMF Volume 12: WLM Volume 13: JES3, JES3 SDSF.